Experimental and numerical investigation of structure and hydrodynamics in packed beds of spherical particles. Issue 5 (23rd February 2018) - Lovreglio, P.; Das, S.; Buist, K. A.; Peters, E. A. J. F.; Pel, L.; Kuipers, J. A. M.
Abstract : In chemical industry, flows often occur in nontransparent equipment, for example in steel pipelines and vessels. Magnetic resonance imaging is a suitable approach to visualize the flow, which cannot be performed with classical optical techniques, and obtain quantitative data in such cases. It is therefore a unique tool to noninvasively study whole‐field porosity and velocity distributions in opaque single‐phase porous media flow. In this article, experimental results obtained with this technique, applied to the study of structure and hydrodynamics in packed beds of spherical particles, are shown and compared with detailed computational fluid dynamics simulations performed with an in‐house numerical code based on an immersed boundary method‐direct numerical simulation approach. Pressure drop and the radial profiles of porosity and axial velocity of the fluid for three packed beds of spheres with different sizes were evaluated, both experimentally and numerically, in order to compare the two approaches. © 2018 The Authors AIChE Journal published by Wiley Periodicals, Inc. on behalf of American Institute of Chemical Engineers AIChE J, 64: 1896–1907, 2018